Conservative Treatment for Acute Ankle Sprain: A Systematic Review - Ortega-Ávila, Ana Belén; Cervera-Garvi, Pablo; Marchena-Rodríguez, Ana José; Chicharro-Luna, Esther; Nester, Christopher; Starbuck, Chelsea; Gijón-Noguerón, Gabriel (MDPI, 2020)
The aim was to identify conservative treatments available for acute ankle sprain and to evaluate their e ectiveness with respect to pain relief and short-term recovery of functional capacity. A systematic review of the relevant literature was conducted via a data search of the PROSPERO, PubMed, Scopus, CINAHL, PyscINFO and SPORTDiscus databases, from inception until December 2019, focusing on randomised control trial studies. Two of the authors independently assessed the quality of each study located and extracted the relevant data. The quality of each paper was assessed using the Cochrane risk of bias tool included in RevMan 5. In all, 20 studies met the inclusion criteria. In terms of absence of bias, only nine papers were classed as “high quality”. Studies (75%) were of low quality in terms of the blinding of participants and personnel and uncertainty in blinding of outcome assessment and all presented one or more other forms of bias. Despite the generally low quality of the studies considered, it can be concluded that conservative treatment for acute ankle sprain normally achieves pain relief and rapidly improved functionality. Research based on higher-quality study designs and procedures would enable more definitive conclusions to be drawn.
Keywords: Tobillos - Lesiones y heridas; Conservative treatment; Systematic Review; Pain; Function; Ankle sprain